The Analysis of Consumer Preference on Product Attributes of Koeliner Ecoe Taro Chip - Dos Reis, Verren Lionyta; Sidharta, Helena; Wiyakusuma, I Bagus Yosia (International Business Management - Universitas Ciputra, 2022)
Consumer preference on the attributes of a product can be useful for company, one of them is to predict the appropriate product for consumers. Company can improve and provide a product based on the choice of attributes that are preferred and desired by consumers so that company can to provide product inventory in accordance with consumer choice. Koeliner Ecoe is one of the UMKM can take the advantage of consumer preference to allocate capital according by the consumers in choosing Koeliner Ecoe taro chip product. The purpose of this research is to know the product attributes that are the most preffered and considered by the consumers in choosing Koeliner Ecoe taro chip product in order to assist the company in arranging improvement strategy and product development of Koeliner Ecoe taro chip in the future. The research site is located in Citraland area, West Surabaya. The sample collection uses purposive sampling technique by distributing questionnaire to respondents as many as 90 people. The analysis model in this research uses conjoint analysis with fractional factorial design approach. The results of this research show that product attribute levels of Koeliner Ecoe taro chip that are the most preferred by the consumers is that using standing pouch doff packaging with sticker one-sided (front) packaging design, the preferred price of Rp 7.000, the selected flavor variant is savory salted with slightly red yellow chip color. The order of important of attribute which affects consumer preference in choosing Koeliner Ecoe taro chip based on important value from the highest value to the lowest value is that price, packaging, packaging design, flavor, chip color.